2021
DOI: 10.1136/bmjopen-2020-046390
|View full text |Cite
|
Sign up to set email alerts
|

RELATE—a randomised controlled feasibility trial of a Relating Therapy module for distressing auditory verbal hallucinations: a study protocol

Abstract: IntroductionAuditory verbal hallucinations (AVHs) are associated with distress and reduced functioning. Research suggests that distress is associated with the voice hearer’s responding to AVH in a passive and subordinate manner. A novel approach focuses on relating to AVH and teaches assertive responses to AVH using experiential role-plays. A small pilot study found a large effect of this approach on AVH distress but an independent multicentre study is required to ascertain effectiveness across different setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The subscales used in this study have demonstrated good reliability (intra‐class correlation coefficient > .93 for distress and > .87 for frequency) (Woodward et al, 2014 ), and they have been used in adult (e.g. Badcock et al, 2020 ; Craig et al, 2018 ; du Sert et al, 2018 ; Hayward et al, 2017 , 2018 ; Jongeneel et al, 2018 ; Lincoln et al, 2021 ; Paulik et al, 2019 , 2018 ) and youth research (Cavelti et al, 2019 ). In this study, internal consistency of PSYRATS‐AH subscales was acceptable (α > .66).…”
Section: Methodsmentioning
confidence: 88%
“…The subscales used in this study have demonstrated good reliability (intra‐class correlation coefficient > .93 for distress and > .87 for frequency) (Woodward et al, 2014 ), and they have been used in adult (e.g. Badcock et al, 2020 ; Craig et al, 2018 ; du Sert et al, 2018 ; Hayward et al, 2017 , 2018 ; Jongeneel et al, 2018 ; Lincoln et al, 2021 ; Paulik et al, 2019 , 2018 ) and youth research (Cavelti et al, 2019 ). In this study, internal consistency of PSYRATS‐AH subscales was acceptable (α > .66).…”
Section: Methodsmentioning
confidence: 88%
“…Reducing the level of psychological distress due to voice-hearing (instead of reducing hearing voices per se) is the main therapy aim of CBTv and the PSYRATS-AH has been widely used in clinical trials investigating the efficacy of CBTv in the past [ 17 , 35 , 36 ]. Additionally, distress is the prioritized outcome by patients with voices and is related to dysfunction [ 37 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…The VAY has good internal consistency and acceptable test-retest reliability [ 80 ]. The psychometric properties of the German version are currently under examination by Lincoln et al [ 37 ].…”
Section: Data Collection and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some emerging evidence that using experiential exercises to recreate hallucinatory episodes within a session may facilitate therapy. For example, in-session role plays [12,13] or audio recordings of things the voice often says [14,15] may be utilised to practise alternative responses. Using in-session exercises may be valuable in helping the person to apply what is discussed in therapy whilst the therapist can support them, aiding transfer to the selfmanagement of hallucinations when encountered in daily life.…”
Section: Psychotherapeutic Interventions Targeting Auditory Hallucina...mentioning
confidence: 99%